The Influence of Heuristic Biases and Risk Propensity on Investment Decisions of the Millennial Generation in Indonesia - Asri Solihat; Nugraha Nugraha; Disman Disman; Ikaputera Waspada (Universitas Pendidikan Indonesia, 2025)
The digital trend during Covid-19 has influenced millennials to invest. Therefore, investors in Bandung have been dominated by millennials. However, researchers believe that millennials are vulnerable in terms of financial prospects. This is because they are easily influenced by biased behavior in investing. In addition, everyone is considered to have inherent psychological biases that prevent them from making rational judgments and risk perceptions that can impact the investment decision-making process. The purpose of this study is to determine the influence of heuristic biases and risk perception on the investment decisions of millennials in Indonesia. The data in this study were analyzed using the Pearson correlation statistical method and linear regression analysis. The results of this study indicate that heuristic biases and risk perception influence the investment decisions of millennials. This study contributes to the existing literature and provides practical implications for investors and the government.